Pipistrellus nathusii ... - Toffoli, Roberto; Culasso, Paola; Locatelli, Andrea G.; Giraudo, Luca (Zenodo, 2016)
Pipistrellus nathusii (Keyserling & Blasius, 1839) Risk Level Europe: Least Concern - LC (Temple & Terry, 2007). Italy: Near Threatened - NT (Rondinini et al., 2013). This species was only identified by bioacoustic analysis at three different localities in Valdieri, Vernante and Limone municipality, where its species-specific social calls were recorded between the end of July and the beginning of September (Fig.4). ... : Published as part of Toffoli, Roberto, Culasso, Paola, Locatelli, Andrea G. & Giraudo, Luca, 2016, Bats of Alpi Marittime Nature Park (North West Italy) and Site of Community Importance IT 1160056: distribution and status, pp. 3-13 in Natural History Sciences 3 (1) on page 10, DOI: 10.4081/nhs.2016.254, http://zenodo.org/record/12523731 ...